Optimization of bus stop spacing for on-demand public bus service - Zhang, Jie (2020)
This paper proposes an optimization model formulation for the design of bus stop spacing of on-demand public bus (ODPB) service. The objective of this model is to minimize the total travel time of all the passengers. To capture the unique characteristics of ODPB service, model constraints such as the length of segment, the configuration of shed line, minimum stop spacing, vehicle capacity limitation, are explicitly considered. Numerical results show that the optimal bus stop spacing for ODPB is very different from a conventional bus. Factors like passenger density, travel time perception weight ratio, access/egress walking speed, and the time loss near/at the stop would affect the ODPB stop spacing significantly.